Trajectory Planning of First Stage Rocket Powered Vertical Recovery Using a Hybrid Optimization Method - XIE Lei; ZHANG Hongbo; ZHOU Xiang; TANG Guojian (Kongzhi Yu Xinxi Jishu)
Standard trajectory design is the basis of rocket recovery guidance law. For this problem, a new hybrid optimization method combining the exterior penalty method, the genetic algorithm (GA) and the sequential quadratic programming (SQP) was proposed. Firstly, the recovery trajectory is divided into five phases: attitude adjustment phase, high-altitude gliding phase, power deceleration phase, atmospheric deceleration phase and powered landing phase. The multi-constraint problem is then transformed into an unconstrained problem by exterior penalty method, and the initial solution can be obtained by GA. Finally, to get a high accuracy optimal solution, a SQP method is employed. Numerical simulation results show that the proposed method can optimize a high accuracy recovery trajectory that satisfies various constraints, and it is simple and effective, which has a great value in the practical applications.